School Culture-Based Internalization of Nationalism and Religious Characters in Islamic Elementary School - Hariyono; Ismail SM; M. Agung Hidayatulloh; Miftachul Huda (Universitas Islam Negeri (UIN) Salatiga, 2023)
The character of nationalism and religion forms the identity of the younger generation, not solely as knowledge but also as manifested in action. This study aims to unveil the culture of nationalism and religious character at Nasima Elementary School (SD Nasima) in Semarang. A qualitative case study methodology involving observation, interviews, and documentation was employed. The findings highlight that school residents perceive nationalism and religion as an environment characterized by nuanced patriotism and religious commitment, shaping the core values of the school. The internalization of nationalism and religious characters is evident through the attitudes and behavior of school residents during commemoration and celebration activities, engagements reflecting nationalism and religious character, appreciation for the diversity of Nusantara culture, and discipline in executing activities related to these characters. The habitual integration of these characters is discernible in various facets, including daily routines, incidental programs, learning activities, extracurricular engagements, and environmental conditions. The results suggest that learning transcends the cognitive domain; character development, as an essential aspect of the affective domain, emerges as a crucial facet in education.